Pixie [videorecording (DVD)] - Cooke, Olivia, 1993-; Fee, Fra, 1987-; Baldwin, Alec, 1958-; Meaney, Colm, 1953- (Paramount, 2021)
On a path to avenge her mother's death, Pixie Hardy attempts a heist that will give her the means to leave her small town life behind. When the plan goes horribly wrong she's forced to team up with a pair of misfits who are clearly in over their heads. On the run from an organized gang, criminal priests, and nuns, led by Father McGrath, the trio will scheme and swindle anyone they come across in this hilarious and thrilling adventure.